Secure Wireless Sensor Networks : Threats and Solutions - Conti, Mauro; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
This book explores five fundamental mechanisms to build secure Wireless Sensor Networks (WSNs). It presents security issues related to a single node which deals with the authentication and communication confidentiality with other nodes. It also focuses on network security, providing solutions for the node capture attack and the clone attack. It examines a number of areas and problems to which WSNs are applied continuously, including: supporting rescue operations, building surveillance, fire prevention, battlefield monitoring and more. However, known and unknown threats still affect WSNs and in many applications of this new technology the security of the network is a fundamental issue for confidentiality, integrity, authenticity and availability. The last section of the book addresses security for a common WSN service. Case studies are provided throughout. Secure Wireless Sensor Networks: Threats and Solutions targets advanced-level students and researchers in computer science and electrical engineering as a secondary text book. Professionals working in the wireless sensor networks field will also find this book useful as a reference. .
Introduction -- Pair-wise key establishment -- Capture Detection -- Clone Detection -- Secure Data Aggregation -- Privacy in Data Aggregation -- Conclusions and Future Works.
Keywords: Computer Communication Networks; Computer security; Telecommunication; Data encryption (Computer science).; Computer Communication Networks; Systems and Data Security; Communications Engineering, Networks; Cryptology